Carrying Capacity of Spherical Hydrostatic Bearings including Elastic Deformation - Shengdong Zhang; Dongjiang Yang; Guangming Li; Yongchao Cheng; Guang Chen; Zhiming Zhang; Jichao Li (Lubricants, 2024)
This paper presents a theoretical model for calculating the carrying capacity of spherical hydrostatic bearings, including the deduction and solution of differential equations for fluid flow in the oil seal and the generation of bearing characteristic parameters. An example is used to verify the accuracy of the proposed calculation model. Additionally, the influence of dynamic pressure on the bearing capacity is investigated under various speed conditions. The results demonstrate that as the minimum width of the oil gap decreases, the maximum dynamic pressure increases non-linearly. Furthermore, the maximum dynamic pressure increases with higher rotational speeds, particularly when the width is smaller.